2004
DOI: 10.1111/j.1474-919x.2004.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of climate change on the reproduction of coastal invertebrates

Abstract: Environmental cues control or synchronize the reproductive cycle of many marine invertebrates. Of these environmental cues, photoperiod and temperature have been shown to moderate reproduction either individually or in combination. In addition, they may act directly or, in the case of photoperiod, set circannual clock mechanisms. These environmental cues may affect a number of reproductive parameters, including sex determination, gametogenesis and spawning. Gonadotrophic and spawning hormones appear to act as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 46 publications
0
70
0
7
Order By: Relevance
“…Lawrence, 2004;Sabaté, 2006;Ward et al, 2007;Webster, 2007). A majority of these studies deal with mass mortalities observed in different coral species and other sessile invertebrates (Perez et al, 2000;Kushmaro et al, 2001;Boyett et al, 2007;Remily & Richardson, 2006;Ward et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lawrence, 2004;Sabaté, 2006;Ward et al, 2007;Webster, 2007). A majority of these studies deal with mass mortalities observed in different coral species and other sessile invertebrates (Perez et al, 2000;Kushmaro et al, 2001;Boyett et al, 2007;Remily & Richardson, 2006;Ward et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature changes can directly influence marine organisms by inducing physiological stress, or by disturbing natural reproductive cycles (Lawrence & Soame, 2004), or they can affect populations indirectly by modifying trophic interactions and competitive relationships (Stenseth et al, 2002). Recent reviews have emphasized the potential importance of parasites and pathogens on populations under global warming (Harvell et al, 2002;Mouritsen & Poulin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Estuaries are defined by salinity change over tidal cycles, but floods (of varying intensity, frequency and duration) can alter salinity regimes dramatically to the detriment of the benthic communities (Ritter et al, 2005). With future climate change, more extreme fluctuations in salinity are expected, which in turn will affect both plant (Short and Neckles (1999) review for seagrass) and faunal communities (Lawrence and Soame, 2004). Ecosystems such as the Mondego estuary will have to deal with the effect of multiple stressors, which may act synergistically to considerable lower the resilience and resistance of the populations to disturbance (Adams, 2005;Cardoso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the shallow depth and relatively weak exchange with the open sea, these systems are particularly vulnerable to eutrophication, recognised as a major problem worldwide (Kennish, 2002;Marques et al, 2003;Pardal et al, 2004;Lillebø et al, 2005;Munkes, 2005;Powers et al, 2005). In addition, global warming and sea-level rise will have important consequences for aquatic ecosystems (Short and Neckles, 1999;Simas et al, 2001;Lawrence and Soame, 2004;Beukema and Dekker, 2005). A major challenge for ecologists is the understanding of the ecosystem functioning and dynamics in the face of natural, anthropogenically-induced and extreme climate variability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the classiWcation of the southern Portuguese benthic fauna as Atlantic-Mediterranean was once more conWrmed in the present study. Nevertheless, as amphipods are sensitive to changes in seawater temperature (e.g., Lawrence and Soame 2004), the distribution patterns of amphipod assemblages are also expected to change in a global warming scenario. In this context, the present study may provide valuable baseline information to ascertain potential future impacts of climate change.…”
Section: Biogeographic Notesmentioning
confidence: 99%